2011
DOI: 10.1016/j.tips.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin-mediated receptor trafficking and signal transduction

Abstract: β-arrestins function as endocytic adaptors and mediate trafficking of a variety of cell-surface receptors, including seven-transmembrane receptors (7TMRs). In the case of 7TMRs, β-arrestins carry out these tasks while simultaneously inhibiting upstream G protein-dependent signaling and promoting alternate downstream signaling pathways. The mechanisms by which β-arrestins interact with a continuously expanding ensemble of protein partners and perform their multiple functions including trafficking and signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
589
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 636 publications
(627 citation statements)
references
References 135 publications
12
589
1
5
Order By: Relevance
“…For example, β-arrestins, which are traditionally recognized as modulators of the desensitization and inactivation of G protein-coupled receptors (GPCRs), have recently been reported to take part in many signaling pathways, independent of G proteins, as scaffold proteins, and this is increasingly being studied [64] . A previous study in our lab indicated that β-arrestin-1, but not β-arrestin-2, induced Beclin1-dependent autophagy in neurons, which revealed a neuroprotective role for β-arrestin-1 in cerebral ischemia.…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…For example, β-arrestins, which are traditionally recognized as modulators of the desensitization and inactivation of G protein-coupled receptors (GPCRs), have recently been reported to take part in many signaling pathways, independent of G proteins, as scaffold proteins, and this is increasingly being studied [64] . A previous study in our lab indicated that β-arrestin-1, but not β-arrestin-2, induced Beclin1-dependent autophagy in neurons, which revealed a neuroprotective role for β-arrestin-1 in cerebral ischemia.…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…One of the many examples that the ubiquitously expressed arrestins serve as more than terminators of receptor signaling through initiating receptor internalization (Groer et al, 2011;Shenoy and Lefkowitz, 2011;Shukla et al, 2011) is the phenotype of mice lacking b-arrestin 2 (b-arr2À/À; Bohn et al, 1999Bohn et al, , 2002Raehal and Bohn, 2011). As morphine does not induce significant internalization of the mu opioid receptor, the effects of morphine in b-arr2À/À mice cannot be explained by this prototypical role of barrestin 2.…”
Section: Introductionmentioning
confidence: 99%
“…Although its main function is the modulation of receptor number on the cell surface, thereby adjusting the sensitivity of the cell to external stimuli, it also plays role in the resensitization and signaling of GPCRs (Ferguson, 2001;Hunyady and Catt, 2006;Shenoy and Lefkowitz, 2011). At the molecular level, β-arrestins are key regulatory proteins of receptor internalization, as they can bind to activated GPCRs, as well as to clathrin and the adaptor protein AP-2, thus directing the receptor towards clathrin-mediated endocytosis (Shenoy and Lefkowitz, 2011). β-arrestins also mediate receptor desensitization, as their binding to the activated GPCRs causes the uncoupling of the receptor from its cognate G protein (Shenoy and Lefkowitz, 2011).…”
mentioning
confidence: 99%
“…At the molecular level, β-arrestins are key regulatory proteins of receptor internalization, as they can bind to activated GPCRs, as well as to clathrin and the adaptor protein AP-2, thus directing the receptor towards clathrin-mediated endocytosis (Shenoy and Lefkowitz, 2011). β-arrestins also mediate receptor desensitization, as their binding to the activated GPCRs causes the uncoupling of the receptor from its cognate G protein (Shenoy and Lefkowitz, 2011). Furthermore, they play important roles in the activation of G proteinindependent signal transduction pathways, e.g.…”
mentioning
confidence: 99%